Empowering lecturers and students with constructivist, community-engaged pedagogies to support Sustainable Development Goals - Gareth A Tribello; Catherine Bates; Caroline McGowan (Irish Journal of Academic Practice)
This reflective paper is a summary of a dialogue between colleagues in TU Dublin and Queen’s University Belfast on addressing the United Nations (UN) Sustainable Development Goals (SDGs) through Community Engaged Research and Learning (CERL). Two of the authors were involved in facilitating an innovative online postgraduate Continuing Professional Development (CPD) module for lecturers who wished to start building CERL into their modules or to develop it further. The third author was a student on this CERL CPD module. The paper was written during a series of meetings between the authors, in which they reflected on their experience of learning and teaching in relation to CERL. Through this dialogue they clarified the importance of rethinking curriculum to include Education for Sustainable Development (ESD), and the unique contribution that CERL as a constructivist pedagogy offers. CERL offers lecturers a way to streamline curriculum by making course content more relevant to students’ lives and to society. Students reflect on and use what they are learning, in collaboration with community partners and lecturers, to deepen their understanding, to develop new competencies, and become more engaged citizens. Furthermore, the authors argue that redesigning the curriculum and embedding the UN SDGs through CERL involves important themes, which may not feature in many university modules. These include building relationships; empathy; process; reflection on practice; time for communication and dialogue; fostering and actively supporting diversity, the understanding of context; and a willingness to demonstrate vulnerability. These are key competencies for achieving the UN SDGs, and CERL supports lecturers, students, and community partners to build them together. The teaching that this approach enables is also enormously rewarding.